Position of Joint Property in Toba Batak Traditional Marriage - Febri Yanti Angela Sinaga; Pieter Radjawane (LUTUR Law Journal, 2025)
Joint property in Batak Toba customs is wealth obtained by both husband and wife since the marriage, both property given as household equipment after the marriage such as panjaean for men and pauseang for women, as well as property from the hard work of husband and wife. Problems occur when the rights of widows who do not have children in the division of joint property in Batak Toba customs often become a problem in family life. This study aims to determine and examine the position of joint property in Batak Toba customary marriages and the procedure for dividing joint property in Batak Toba customary marriages that do not have children. Through normative legal methods with qualitative methods. Based on this study, the position of joint property in Batak Toba customary marriages is basically no separation of joint property and inherited property. All property included in the marriage bond becomes joint property. The position of joint property according to Batak Toba customs in marriage is the joint property of husband and wife. The procedure for dividing joint property in Batak Toba customary marriages that do not have children involves decisions based on customs and family deliberations. Batak Toba customs do not recognize the procedure for dividing by calculation but are based on considerations, considering the form of objects and the needs of the heirs concerned. Batak Toba customs if the husband dies and does not have children, the joint property obtained during the marriage will belong to the husband's family.